Networking all-in-one for dummies - Lowe, Doug, 1959- (--For dummies., 2013)
This one handy book covers all the essentials you need to know about running a network. It explains how to set up and use a computer network, including installing network hardware, administration and security, TCP/IP, wireless networking, mobile networking, Windows Server 2012 reference, and managing Linux systems.